2013
DOI: 10.1016/j.ijsu.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiological incidence of parastomal herniation in cancer patients with permanent colostomy: What is the ideal size of the surgical aperture?

Abstract: The majority of patients with a permanent colostomy develop a parastomal hernia within the first two post-operative years. Parastomal herniation appears unlikely to develop with an abdominal wall defect diameter ≤25 mm provided this does not enlarge with time. Surgical techniques that utilise stapling devices to form a 'custom-made' and rigid trephine might reduce the herniation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Other factors in the literature that have been suggested but not validated include malnutrition, smoking status, chronic coughing, chronic constipation, ascites, corticosteroid use, and postoperative wound sepsis [21]. Technical aspects related to ostomy creation that have been suggested as risk factors for PSH include bringing the stoma out through the resection site [9], an intraperitoneal route as opposed to an extraperitoneal one [7,31,32,33], a laparoscopic approach [31], and increased aperture size [10,29,34]. …”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors in the literature that have been suggested but not validated include malnutrition, smoking status, chronic coughing, chronic constipation, ascites, corticosteroid use, and postoperative wound sepsis [21]. Technical aspects related to ostomy creation that have been suggested as risk factors for PSH include bringing the stoma out through the resection site [9], an intraperitoneal route as opposed to an extraperitoneal one [7,31,32,33], a laparoscopic approach [31], and increased aperture size [10,29,34]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…Funahashi et al reported a laparoscopic approach as an independent risk factor [31], but no randomized trials comparing a laparoscopic and open approach have been performed. Hotouras et al suggest making the aperture size ≤25 mm in size based on an observational study comparing the aperture size and presence of PSH on CT scan in 43 patients undergoing permanent colostomy for malignancy [34]. However, there have been no clinical trials to date evaluating the ideal aperture size and subsequent risk of PSH.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several biological studies have shown moderate levels of wound infection effectively treated conservatively (3-26 %), low recurrence (13-15 %) and low morbidity [18][19][20][21][22]. The possibility of leaving mesh in situ in an infected field is enticing, but a major argument against its use is cost with biologic mesh reported to be about 10 times more expensive than synthetic mesh [7]. There is still a large knowledge gap regarding comparative costs and functional outcomes between these materials, as well as a dearth of truly longterm outcome data.…”
Section: Synthetic Versus Biologic Prosthesesmentioning
confidence: 99%
“…The risk of developing PH has been suggested to be lower after ileostomy than after a colostomy (1-28 % for an ileostomy, 4-48 % for colostomy), with high rates of incisional hernias after colostomy closure [2,3,5,6]. Most hernias develop within 2 years of stoma formation [5][6][7], are asymptomatic and do not require intervention. However, 10-30 % of ostomates have been reported to require surgical intervention [3,5,6], and some studies even report rates as high as 70 % [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation